THE ROLE OF BRAND IMAGE AND PERCEIVED RISK ON THE ATTITUDE AND INTENTION TO USE PAYLATER SERVICES IN GENERATION Z. - Susilo, Amanda; Dewi, Yuli; Whyte, Frances (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study investigates the impact of Brand Image and Perceived Risk on Attitude and Intention to Use Paylater services among Generation Z in Indonesia's growing financial technology landscape. Paylater, a widely adopted service, facilitates cashless fulfilment of needs. This study focusing on Generation Z which domicile in Java Island Indonesia. The aim of this study is to elucidate Paylater's significance as an emerging financial solution, providing insights to manage user risks and enhance understanding of consumer decision-making processes. Data from 125 respondents collected via questionnaires and analysed using Partial Least Square (PLS), the study reveals significant associations that the existence of Brand Image has significant impact to attitude and attitude is significant to Intention to use Paylater. This path are the most important variables that has greatest value impact to influence Paylater’s intention to use. However, Brand Image's impact on Intention to use Paylater is insignificant. The existence of Perceived Risk significantly influences Attitude. The result also prove that brand image and perceived value are not directly significant to paylater’s intention to use.